Cross-Bridged Cyclam with Phosphonate and Phosphinate Pendant Arms: Chelators for Copper Radioisotopes with Fast Complexation - Pazderová, Lucia; David, Tomáš; Hlinová, Veronika; Plutnar, Jan; Kotek, Jan; Lubal, Přemysl; Kubíček, Vojtěch; Hermann, Petr (Inorganic chemistry, 2020)
Cross-bridged cyclam derivatives bearing two phosphonate (H4L1), bis(phosphinate) (H4L2), or phosphinate (H2L3) pendant arms were synthesized and studied with respect to their application as copper radioisotope carriers in nuclear medicine. The ligands show high macrocycle basicity (pK1 > 14) and high Cu(II) complex stability (log K = 20-24). The complexation and dissociation kinetics of the Cu(II) complexes were studied by ultraviolet-visible spectroscopy. Phosphonate Cu(II)-H4L1 and bis(phosphinate) Cu(II)-H4L2 complexes form very quickly, reaching quantitative formation within 1 s at pH ∼6 and millimolar concentrations. Conversely, the formation of the phosphinate complex Cu(II)-H2L3 is much slower (9 min at pH ∼6) due to the low stability of the out-of-cage reaction intermediate. All studied complexes are highly kinetically inert, showing half-lives of 120, 11, and 111 h for Cu(II)-H4L1, Cu(II)-H4L2, and Cu(II)-H2L3 complexes, respectively, in 1 M HClO4 at 90 °C. The high thermodynamic stability, fast formation, and extreme kinetic inertness of Cu(II) complexes indicate that phosphonate and bis(phosphinate) derivatives are promising ligands for nuclear medicine.